Japan and Trans-Pacific Partnership Impact on the Development of Cooperation within SCO - A. Ivanov (Международная аналитика, 2015)
Factors of interest of Japan towards Central Asian and SCO countries as well as possibilities of inclusion of Japan into geopolitical agenda of SCO are analyzed. Prospects of interrelations in USA-Japan-China triangle are under examination in the paper.